2013
DOI: 10.5114/wo.2013.35033
|View full text |Cite
|
Sign up to set email alerts
|

Reviews Palliative care in patients with lung cancer

Abstract: Lung cancer accounts for 12% of all cancers and has the highest annual rate of mortality in men and women. The overall aim is cure or prolongation of life without evidence of disease. Almost 60% of patients at the moment of diagnosis are not eligible for radical treatment. Therefore soothing and supportive treatment is the only treatment of choice. Patients with lung cancer who have symptoms of dyspnea, chronic cough, severe pain, exhaustion and cachexia syndrome, fear and depression and significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
0
22
0
3
Order By: Relevance
“…This is consistent with the trends across the globe; palliative care only improves symptom free survival and quality of life; however, it provides no benefit on survival duration. 9 Multiple studies have documented improved prognosis and better overall survival in nonsmoking NSCLC patients. Indeed, in our study, the median survival among NSCLC patients who are/were smokers was 4 months with range of 3.3 to 4.7 months, whereas in nonsmoker NSCLC group, it was 9 months with range of 6.1 to 11.9 months.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the trends across the globe; palliative care only improves symptom free survival and quality of life; however, it provides no benefit on survival duration. 9 Multiple studies have documented improved prognosis and better overall survival in nonsmoking NSCLC patients. Indeed, in our study, the median survival among NSCLC patients who are/were smokers was 4 months with range of 3.3 to 4.7 months, whereas in nonsmoker NSCLC group, it was 9 months with range of 6.1 to 11.9 months.…”
Section: Discussionmentioning
confidence: 99%
“…Lung and the associated respiratory system is the prime target of the inhaled contaminated air which include pollutants and carcinogens like B(a)P that have been established as important etiological agents in causation of lung cancers (39). Majority of lung cancers are diagnosed at late stages when the options for treatment are mostly palliative (40). Management of lung cancer requires monitoring of the tumor burden to determine the response to treatment and therefore, improved biomarkers are…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the second hand smoking of radon and particulate matters related to air pollution agents such as benzene (44), formaldehyde (44) and diesel air pollutants (45) are other identified sources of lung cancer. The symptoms include consistent coughing, concise and interrupted breath, puffing sound, bloody spittle, continuous bronchitis and other chest pain related issues (46). Subjects with small cell lung cancer (SCLC) were reported to have stronger initial response to chemotherapy than those with non-small cell lung cancer (NSCLC) (47,48) although they are both responsible for eighty-five percent of lung cancer (47).…”
Section: Types Of Cancermentioning
confidence: 99%